2016
DOI: 10.1177/0706743716648290
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Oxidative Phosphorylation System (OXPHOS) Deficits in Schizophrenia

Abstract: Mitochondria are key players in the generation and regulation of cellular bioenergetics, producing the majority of adenosine triphosphate molecules by the oxidative phosphorylation system (OXPHOS). Linked to numerous signaling pathways and cellular functions, mitochondria, and OXPHOS in particular, are involved in neuronal development, connectivity, plasticity, and differentiation. Impairments in a variety of mitochondrial functions have been described in different general and psychiatric disorders, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 202 publications
(252 reference statements)
2
83
0
Order By: Relevance
“…These reductions might be the result of an overrepresentation of subjects with chronic antipsychotic medication that reduces complex I activity. To date, very few studies of deficits in complex I have been reported in medication-free subjects as reviewed [5,6,42]. The reports of a deficit in complex I are found in studies of medicated subjects, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These reductions might be the result of an overrepresentation of subjects with chronic antipsychotic medication that reduces complex I activity. To date, very few studies of deficits in complex I have been reported in medication-free subjects as reviewed [5,6,42]. The reports of a deficit in complex I are found in studies of medicated subjects, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies of the frontal cortex of subjects with BD [41] and SZ [42] have reported reductions in complex I activity. These reductions might be the result of an overrepresentation of subjects with chronic antipsychotic medication that reduces complex I activity.…”
Section: Discussionmentioning
confidence: 99%
“…The triphosphate synthetase inhibitor is, for example, oligomycin. Then, by adding an appropriate concentration of the anti-coupling agent, the mitochondria are allowed idling to limit the maximum oxygen consumption capacity of the mitochondria (Maximal Respiration) without destroying the electron transport chain of the mitochondrial inner membrane [4]. The anti-coupling agent is Carbonylcyanide-4-(trifluoromethoxy) phenylhydrazone (FCCP).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative injury and functional impairment may act an early and important role in the development of age-related macular degeneration (AMD) [2,4,5,6], Previous studies have indicated that damage to RPE through photochemical mechanisms by free radical reactions is driven by photo-excited, endogenous chromophores through the cornea and lens [2]. As we age, the yellow pigment accumulates; however, oxidative damage increases, antioxidant capacity decreases and the efficiency of self-repairing systems deteriorate during the aging process.…”
Section: Introductionmentioning
confidence: 99%
“…In support of OXPHOS dysfunction in SCZ, a small parallel transcriptomic, proteomic, and metabolomic study found OXPHOS to be the most significantly downregulated pathway in patients compared to controls [74]. More details on the role of the OXPHOS pathway in the context of SCZ pathophysiology can be found in a recent review [75]. …”
Section: Mitochondrial Pathwaysmentioning
confidence: 99%